2005
DOI: 10.1111/j.1464-410x.2006.05915.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of varicocele by a subinguinal approach combined with antegrade intraoperative sclerotherapy of venous vessels

Abstract: vein in the spermatic cord fat was cannulated. A 7-9 cm segment of the spermatic cord was clamped for 8-10 min; at the start of the ischaemia time, 1.5-3 mL of 3% atoxysclerol was injected into the cannulated vein. After sclerotherapy, the vein was ligated at the injection site, and the blood flow to the cord was restored. RESULTSThe mean operative duration was 25 min. Follow-up at 3 and 6 months after surgery, with objective examination and scrotal ultrasonography, revealed one case of clinical recurrence/per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The mean intervals from surgery to improvement in semen parameters and to spontaneous pregnancy were reported to be approximately 5 and 7 months, respectively [59]. However, a recent study at Kobe University reported earlier improvement in sperm DNA integrity after microsurgical repair of varicoceles [60].…”
Section: New Role Of Varicocele Repair In the Art Eramentioning
confidence: 99%
“…The mean intervals from surgery to improvement in semen parameters and to spontaneous pregnancy were reported to be approximately 5 and 7 months, respectively [59]. However, a recent study at Kobe University reported earlier improvement in sperm DNA integrity after microsurgical repair of varicoceles [60].…”
Section: New Role Of Varicocele Repair In the Art Eramentioning
confidence: 99%
“…From April 2004 to September 2005, we diagnosed 25 cases of left varicocele with concomitant testicular hypotrophy; published reports suggest that a difference of 1 25% of testicular volume is considered as testicular hypotrophy [5] . The mean age of the patients was 14.4 years.…”
Section: Methodsmentioning
confidence: 99%
“…Duration and severity of varicocele may be a risk factor for infertility related with age in patients with varicocele (7). The mean time for semen improvement and spontaneous pregnancy after surgery is approximately five to seven months, respectively (8). However, the aetiology of underlying infertility is especially uncertain in men whose semen parameters do not significantly improve or do not achieve pregnancy following varicocele surgery.…”
Section: Introductionmentioning
confidence: 99%